Bound Water, Phase Configuration, and Dielectric Damping Effects on TDR‐Measured Apparent Permittivity - Dyck, M. (2020)
The main objective of this work was to investigate the influence of bound water and phase configuration in four, high‐surface‐area Japanese Andisols with bimodal pore‐size distributions using dielectric mixing models alone or coupled with a dielectric damping model. Soil‐specific Ka(θ) relationships were measured in the laboratory using standard methods and were simulated with two frequency‐independent, real‐valued dielectric mixing models and a complex‐valued, frequency‐dependent model coupled with a dielectric damping model. The results of the simulations indicate that frequency‐dependent dielectric permittivity of the bound water phase significantly influences TDR‐measured Ka(θ), suggesting that soil‐ and probe‐specific calibrations may be required for soils with significant volumetric fractions of bound water.